2016
DOI: 10.1021/acs.nanolett.6b04146
|View full text |Cite
|
Sign up to set email alerts
|

3D DNA Origami Cuboids as Monodisperse Patchy Nanoparticles for Switchable Hierarchical Self-Assembly

Abstract: The rational design of anisotropic interaction patterns is a key step for programming colloid and nanoparticle self-assembly and emergent functions. Herein, we demonstrate a concept for harnessing the capabilities of 3D DNA origami for extensive supracolloidal self-assembly and showcase its use for making truly monodisperse, patchy, divalent nanocuboids that can self-assemble into supracolloidal fibrils via programmable DNA hybridization. A change in the number of connector duplexes at the patches reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 32 publications
2
71
0
3
Order By: Relevance
“…However,t hey can serve to precisely attach and arrange inorganic nanoparticles. [211,212] Besides the development of further aerogel materials and to take the existing results to alarger scale,this field has now the potential to focus on amore targeted progress.T aking the library of available nanoparticles and assembling them into aerogels allows for as pecific tuning of their final properties. [208,209] TheS eidel group even showed that the inorganic nanostructures obtained still have an intact DNAshell, which makes it possible to assemble them in acontrolled manner.…”
Section: Discussionmentioning
confidence: 99%
“…However,t hey can serve to precisely attach and arrange inorganic nanoparticles. [211,212] Besides the development of further aerogel materials and to take the existing results to alarger scale,this field has now the potential to focus on amore targeted progress.T aking the library of available nanoparticles and assembling them into aerogels allows for as pecific tuning of their final properties. [208,209] TheS eidel group even showed that the inorganic nanostructures obtained still have an intact DNAshell, which makes it possible to assemble them in acontrolled manner.…”
Section: Discussionmentioning
confidence: 99%
“…[64] The topography of the patterned substrate provided a sufficient bias to control the long-range order of the block copolymer. [70][71][72][73] When the DNA assembly is precisely controlled by using a patterned surface, DNA origami can be a powerful tool, for example, by dictating the arrangement of sub 10 nm components (gold nanoparticles) over large scale areas ( Figure 2C). [63][64][65][66] Template-directed assembly of molecules, DNA, and nanoparticles can also give rise to micro and nanoscale structures with promising optical responses.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…As the monodisperse nanoparticle, we employ a bivalent 3D DNA origami cuboid . It is folded from a m13mp18 cyclic scaffold ssDNA and a 5‐fold excess of ssDNA staple strands in a temperature ramp and purified by membrane spin‐filtration to remove excess staple strands (Figure a).…”
Section: Figurementioning
confidence: 99%